Respuesta :

Answer: -4

Step-by-step explanation:

3-9=-6

-6*5=-30

-30-1=-31

6*-31=-186

-186+2=-184

8-2=6

6*7=42

42+4=46.

-184/46=-4

Answer and Step-by-step explanation:

All you have to do is follow the order of operations.

We do everything in the first set of parenthesis, then we work our way out.

[tex]\frac{6(5(3-9)-1) + 2}{7(8-2)+4}[/tex]

First, we would subtract 9 from 3, and 2 from 8.

3 - 9 equals -6

8 - 2 equals 6

[tex]\frac{6(5(-6)-1) + 2}{7(6)+4}[/tex]

Now, we multiply those numbers.

5 times -6 equals -30

7 times 6 is 42

[tex]\frac{6(-30 -1) + 2}{42+4}[/tex]

Now, we simplify.

-30 minus 1 equals -31

42 + 4 equals 46

[tex]\frac{6(-31) + 2}{46}[/tex]

Multiply -31 by 6, then add 2 to the product.

-31 times 6 equals -186

-186 plus 2 equals -184

[tex]\frac{-184}{46}[/tex]

Finally, we divide.

-184 divided by 46 equals

-4

-4 is the answer to the expression.

I hope this helps!

#teamtrees #PAW (Plant And Water)

ACCESS MORE